Contemporary Islamic Education in a Global Perspective: A Comparative Study of the National University of Singapore and Seoul National University - Vitasari, Dian; Sassi, Komarudin; Harun, Makmur (Institut Agama Islam Negeri Kediri, 2024)
Islamic education faces complex challenges and opportunities in the era of globalization. This comparative study between the National University of Singapore (NUS) and Seoul National University (SNU) offers an interesting perspective on how two leading universities in Southeast Asia and Northeast Asia are developing Islamic studies programs that are relevant to social, cultural and religious contexts. This research aims to analyze the implementation of learning that is able to contribute to community development. The research method uses relevant literature studies with data sources from journal articles, books and official documents from both universities. The research approach uses descriptive analysis by understanding the differences and similarities implemented by these two institutions. Data analysis techniques use comparative studies, comparing various sources to find similarities, differences and relationships between concepts. The research results show that NUS and SNU have different approaches in integrating Islamic values into the curriculum. NUS places greater emphasis on the relevance of Islam to Singapore's multicultural context, while SNU focuses more on the roots of Islamic traditions. The two universities also have differences in terms of teaching methods, where NUS adopts a more interactive and problem-based approach, while SNU still maintains traditional teaching methods.